The Effect of (Tabata) Style Exercises to Developing Endurance Ability and Performance of the Skill of Lay-Up Shot of Basketball for Young Players Under Age 18 Years - Ahmed Ghassy Abd Alhussein; Hussein Mnaty Sachit; Nidahal Obaid Hamza (Indian Journal of Forensic Medicine & Toxicology, 2021)
The researchers used the experimental method of experimental design with pre and post-test for oneexperimental group for its suitability to the nature of the research, the research community was identifiedwith young basketball players belonging to the Al-Ghadriyah Sports Club of (16-18) years for the 2020-2021 training season, which totaled 12 players. The research sample was chosen by (7) players representingthe training group, and 5 players were hired for the experiment, the researchers prepared his exercises ina high-intensity interval training method and repetitive training in order to achieve the goal of reachingthe development of endurance and performance of the skill of lay-up shot among the players of the Al-Ghadriyah sports club in basketball in Kerbala. The application of the exercises continued for (8) weeks, inwhich 16 training units were achieved, the total number of training units included exercises in the (Tabata)style (16) units and the number of weekly training units that included exercises in the (Tabata) style (2)units for a period of (8) weeks, the time of exercises in one training unit (11-15) minutes. The intensity usedranges between 90-100 %. Among the most important conclusions reached by the researchers is the presenceof statistically significant differences between the results of the pre and post-tests of the experimental groupin the researched variables, which indicates that the (Tabata) exercises are effective in developing enduranceand performing the skill of lay-up shot of basketball.